Impact of balloon inflation on the insertion of endoscopic ultrasound: a prospective, randomized controlled trial - Kang, Jinwoo; Lee, Sang Hyub; Lee, Jae Woo; Jang, Dong Kee; Choi, Jin Ho; Choi, Young Hoon; Paik, Woo Hyun; Ahn, Dong-Won; Jeong, Ji Bong; Ryu, Ji Kon; Kim, Yong-Tae (Endoscopy International Open, 2020)
Background and study aims During endoscopic ultrasound (EUS), patients may experience severe discomfort. The radial echoendoscope has a balloon around its tip. Balloon inflation prior to insertion may reduce contact injury and pharyngeal pain. The purpose of this study was to investigate the effect of balloon inflation on pharyngeal pain during insertion. Patients and methods Patients who underwent radial EUS for pancreatobiliary disease were randomized into standard insertion or balloon-inflated insertion. The primary outcome was the proportion of moderate-to-severe pharyngeal pain. Secondary outcomes were the degree of pharyngeal pain, risk factors for moderate pharyngeal pain, procedure-related adverse events, and pharyngeal pain depending on the experience of the endoscopist. Results A total of 481 patients were randomized into two groups: standard insertion (238) and balloon inflation (243). No statistically significant differences in proportion of moderate-to-severe pain were found (26.5 % vs. 20.2 %, P = 0.107). Balloon inflation (HR 0.65; 95 % CI (0.42–0.98, P = 0.041) was a protective factor against moderate pain. Balloon inflation reduced the proportion of patients with moderate-to-severe pain when performed by physicians with less than 3months of experience with EUS (44.7 % vs. 25.3 %, P = 0.012).Conclusion Balloon inflation did not reduce the absolute degree of post-procedural pain with EUS, but it reduced the number of patients with moderate-to-severe pain when performed by physicians with less than 3 months of experience.